Energy Security as a Key Driving Factor for Socioeconomic Development: From Mitigation to Solution - Pawlowska, Barbara; Cirella, Giuseppe T. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book looks at the increasing demand for energy of contemporary societies and economies from around the world. Energy is the driving force behind development. As such, the future challenge will be not only to meet the rising demand but also to implement less reliance on depleting fossil fuels, which cause damage to the environment. Moreover, the sustainability of supplied energy requires a reduction of emissions to control the absorption capacity vis-à-vis the environment. Globally, policymakers have largely recognized the significance of the relationship between energy and economic progress. Policymakers usually consider the social and economic aspects of energy security in terms of affordability and accessibility of service. The conditions of socioeconomic development depend on safe, secure, and sustainable energy at affordable prices. One of the prime concerns of policymakers should be to ensure energy security at the national level. These factors result in an increasing interest in undertaking activities in developing renewable resources. Energy efficiency is treated as the most cost-effective way to reduce energy demand while maintaining stable economic activity. Increasing energy efficiency is an important contributive aspect to solving issues in relation to climate change, energy security, and energy competitiveness. As a result, no country can afford to waste energy-giving rise to this Special Issue of "Energy Security as a Key Driving Factor for Socioeconomic Development: From Mitigation to Solution" in the journal Energies.